Coinfection of SARS-CoV-2 with other respiratory pathogens in outpatients from Ecuador - Diana Morales-Jadán; Claire Muslin; Carolina Viteri-Dávila; Barbara Coronel; Bernardo Castro-Rodríguez; Alexander Paolo Vallejo-Janeta; Aquiles Rodrigo Henríquez-Trujillo; Miguel Angel Garcia-Bereguiain; Ismar A. Rivera-Olivero (Frontiers Media S.A., 2023)
Worldwide, the COVID-19 pandemic caused by SARS-CoV-2 has enormously impacted healthcare systems, especially in low and middle-income countries. Coinfections with respiratory pathogens in COVID-19 patients may contribute to worse outcomes. This study identified the presence of 12 viral coinfections and pneumococcal carriers among individuals with SARS-CoV-2 infection in outpatient and community settings in Ecuador. From January 2020 to November 2021, 215 nasopharyngeal and nasal swabs were taken from individuals who reported symptoms of COVID-19 or had known exposure to someone with confirmed or suspected COVID-19. One hundred fifty-eight tested positive for SARS-CoV-2 by RT-qPCR and coinfections were detected in 12% (19/158) of SARS-CoV-2-positive patients; the most frequent coinfection was with influenza A virus at 4.4% (7/158; 95% CI: 1.2-7.6), followed by respiratory syncytial virus with 3.1% (5/158; 95% CI: 0.4-5.8), and finally rhinovirus and human coronavirus NL63 with 1.2% (2/158). Pneumococcal carriage was detected in 3.7% (6/158; 95% CI: 0.76-6.64) of SARS-CoV-2 cases. Influenza B, adenovirus, human metapneumovirus (HMPV), parainfluenza virus types 1, 2, and 3, and human coronavirus HKU1 were undetected. To our knowledge, this is the first study of coinfection of SARS-CoV-2 and respiratory pathogens performed on outpatients in Latin America. The high proportion of outpatients with viral coinfections reported in our cohort allows us to suggest that testing for SARS-CoV-2 and other common respiratory pathogens should be carried out to ensure accurate diagnoses, prompt patient treatment, and appropriate isolation.